2019
DOI: 10.5603/njo.2019.0028
|View full text |Cite
|
Sign up to set email alerts
|

A squamous cell carcinoma arising from scrotal epidermal cyst. A case report and review of 94 cases from the world literature

Abstract: Epidermal cysts are a common benign skin abnormality, comprising 85-90% of all excised skin cysts. The term epidermal inclusion cyst refers specifically when the cyst resulted from the implantation of epidermal elements in the dermis. Squamous cell carcinomas (SCCs) are common skin lesions; however, a malignant transformation of an epidermal cyst is very rare with incidence of 0.011-0.045%. Few cases of malignant transformation of an epidermal cyst have been reported in the literature so far. This paper presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The presence of keratinized material in the urine sample suggests an epidermoid cyst in the urinary tract [5] . ECs are usually benign, however, a few cases with MT have been reported in the literature with a reported rate up to 0.045% [1] , [8] , [9] . SqCC arising in an EC is rarely suspected in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The presence of keratinized material in the urine sample suggests an epidermoid cyst in the urinary tract [5] . ECs are usually benign, however, a few cases with MT have been reported in the literature with a reported rate up to 0.045% [1] , [8] , [9] . SqCC arising in an EC is rarely suspected in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In a long-standing EC, the MT can occur suddenly with some abnormal changes in the cyst including; a firm mass replacing the cyst, increase in size, discharge, pain, ulceration and bleeding inside the cyst which do not response to conservative treatment [7] , [10] , [12] . In a series of 94 cases of SqCC arising in EC reported, the most common site were head and neck (55%) followed by lower limb (13%), trunk (13%), perineum (8%) and upper limb (6%) with a slightly males' predominance (65%) [1] . Another review of 19 cases of SqCC arising in EC showed that majority of those cases were in males and the age ranged from 20 to 80 years old with mean age of 43.2 years [13] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations